Association Between Partial Pressure of Carbon Dioxide and Immediate Seizures in Patients With Primary Intracerebral Hemorrhage: A Propensity-Matched Analysis - Pan, Zhiming; Zhong, Qiuli; Wang, Chaoying; Wang, Jianqun; Chen, Xiaoyan; Li, Xiaoyan; Zhang, Xintong; Zhang, Yibin (Frontiers in Neurology, 2022)
Purpose: To explore the value of partial pressure of carbon dioxide (PaCO2) levels in arterial blood for predicting immediate seizures (ISs) in patients with primary intracerebral hemorrhage (ICH). Methods: Demographic information and clinical data from patients with primary ICH were prospectively collected, including arterial blood gas analysis. Immediate seizures (ISs) were determined as seizures in the first 24h after admission. Univariate and multivariate analyses were performed to assess the association of PaCO2 levels with ISs. Propensity-score matching (PSM) analyses were adopted to reduce the baseline difference between ISs and non-ISs groups. Results: A total of 596 primary ICH patients were initially screened in this clinical study, 368 of whom fulfilled all the inclusion criteria (mean age, (60.46 ±12.78) years; 57.9% female patients). ISs occurred in 30 of 368 (8.15%) primary ICH patients of this cohort. Patients with ISs had significantly lower PaCO2 levels [34.35(32.38-37.53) vs. 39.45(35.90-43.43), mmHg, p<0.001], and younger age than those without ISs ((54.57±12.15 vs. 60.99 ±12.72, yrs, p=0.008). Multivariate analysis showed that lower initial PaCO2 (≤37.2mmHg) level was a significant independent predictor of ISs (OR 0.141, 95% CI 0.057-0.351, p<0.001), as well as younger age (OR 0.961, 95% CI 0.928–0.995, p=0.023) and HE (OR 0.340, 95% CI 0.134–0.863, p=0.023). Receiver operating characteristic curve (ROC) analysis demonstrated that the optimal cutoff value of PaCO2 level for predicting ISs was 37.20 mmHg in primary ICH patients (the area under the curve (AUC) was 0.760 with a corresponding sensitivity of 76.67% and specificity of 67.46%, 95%CI=0.713-0.802, p<0.001). After PSM, the matched ISs group had significantly lower PaCO2 levels compared with the matched non-ISs group [34.45(32.43-38.18) vs. 41.75(35.85-43.98), mmHg, p <0.05) in the univariate analysis. The lower initial PaCO2 level was still independent of ISs following primary ICH. Conclusions: The lower initial PaCO2 level was associated with an increased risk of ISs in primary ICH patients.